Alfred Zimmern’s early political thought I: idealism, internationalism, and the study of ancient history - Rood, T (Imprint Academic, 2025)
This is the first of two articles analysing the intellectual formation of Alfred Zimmern, a leading figure in the study of International Relations in the first half of the twentieth century. Drawing on many archival sources, it argues against claims in recent scholarship that Zimmern was strongly influenced by the Idealism popular at Oxford at the time he read Literae Humaniores. Instead, it sets Zimmern’s concerns in the context of the emerging social sciences and argues that it was the study of Ancient History rather than Philosophy that shaped his early internationalist thought. The article as a whole studies disciplinary methodology in the writing of intellectual history.